Consequences of Rejecting the Principle of Portie Legitieme on Wills and Deeds of Grants - Setiyowati Setiyowati; Edy Lisdiyono (Susbtantive Justice International Journal of Law, 2023)
Inheritance law in the BW is basically regulatory and there is no element of coercion. The heir has the right to do anything with his property as long as he is still alive. However, the treatment of his assets must not violate the legitimacy of the portie or the absolute rights of the legal heirs. If the right of legitieme portie is violated, all the actions of the heirs are null and void as long as the demands of the heirs are valid. The purpose of this research is to find out the legal consequences of annulment of wills and awarding of deed for violating the legitieme portie. The method of analysis was carried out using a case study of the Supreme Court Decision. The results of the analysis of the case filed a lawsuit for Budijono Hartono's inheritance between Budijono Hartono's legitimate child as the legal heir and Budijono Hartono's wife, the Court judge decided to cancel the Will and Grant Deed for violating the legitieme portie, as a consequence of not fulfilling the provisions in the laws and regulations on the seduction of legitimaries. Deeds of wills and deed of grants are declared to have no legal force so that all assets listed in the deed of wills and grants are included in the boedel to be divided among all the heirs.